2015
DOI: 10.1007/s00520-015-2772-z
|View full text |Cite
|
Sign up to set email alerts
|

Fecal ESBL Escherichia coli carriage as a risk factor for bacteremia in patients with hematological malignancies

Abstract: Fecal colonization by ESBL-EC is associated with increased risk of BSI by this strain, longer hospital stay, and higher related costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 30 publications
7
45
0
Order By: Relevance
“…94 Fecal colonization with resistant strains is related to an increased probability of BSIs caused by the same bacteria and the relative risk ranged from 3.4 to 4.5 for ESBL-producing E. coli. 95,96 Prophylaxis of bloodstream infection and fever during neutropenia Isolation of neutropenic patients in single rooms, observance of contact precautions and basic hygiene procedures are essential, but not sufficient, steps in infections prevention. Chemoprophylaxis is defined as administration of antibiotic agents to patients at risk for infectious complications but without any suggestive signs or symptoms, in order to prevent bacterial infection (Table 1).…”
Section: Othersmentioning
confidence: 99%
“…94 Fecal colonization with resistant strains is related to an increased probability of BSIs caused by the same bacteria and the relative risk ranged from 3.4 to 4.5 for ESBL-producing E. coli. 95,96 Prophylaxis of bloodstream infection and fever during neutropenia Isolation of neutropenic patients in single rooms, observance of contact precautions and basic hygiene procedures are essential, but not sufficient, steps in infections prevention. Chemoprophylaxis is defined as administration of antibiotic agents to patients at risk for infectious complications but without any suggestive signs or symptoms, in order to prevent bacterial infection (Table 1).…”
Section: Othersmentioning
confidence: 99%
“…A multivariate analysis showed that ESBL-E colonization was the most important risk factor for ESBL-E BSI. Other investigators found that 22% of patients with hematologic malignancies who were colonized with ESBL-producing E. coli (ESBL-EC) developed subsequent ESBL-EC bacteremia [109]. A multicenter study of HSCT recipients in Italy also identified high rates of colonization to infection for CRKP.…”
Section: Improving Outcomes Once Infectedmentioning
confidence: 99%
“…80 Investigators in Mexico city evaluated the impact of fecal colonization with extended-spectrum b-lactamase-producing E coli for BSI, clinical outcome, and costs in patients with hematologic malignancies and severe neutropenia. 51 Colonization Treatment Challenges in the Immunocompromised Host with ESBL E coli increased the risk of BSI by the same strain (relative risk, 3.4; 95% CI, 1.5-7.8; P 5 .001), shorter time to death (74 AE 62 vs 95 AE 83 days; P < .001), longer hospital stay (64 AE 39 vs 48 AE 32 days; P 5 .01), and higher infection-related costs ($6528 AE $4348 vs $4722 AE $3173; P 5 .01). There was no difference in overall mortality between the groups.…”
Section: Risks For Multidrug-resistant Organisms In the Febrile Neutrmentioning
confidence: 97%
“…In university hospitals in Italy, high rates of P aeruginosa BSIs (20% of all BSI) were observed in febrile neutropenic patients, with 33% to 70% MDR PSDA isolates reported. 61,62,65,66 Other centers have reported increasing rates of MDR A baumannii and other ESKAPE pathogens, 6,50,51,57,65 including carbapenem-resistant K pneumoniae (35%). 61 Garza-Ramos and colleagues 67 also described a high prevalence of ESBL and GES carbapenemases in carbapenem-resistant P aeruginosa in their hospitals.…”
Section: Prevalence Of Multidrug-resistant Organisms In Cancer Patienmentioning
confidence: 98%
See 1 more Smart Citation